Hail Windsor crowned with lofty towers - Abingdon, James Bertie Earl of 1653-1699; Salomon, Johann Peter 1745-1815; Dibdin, Charles 1745-1814 (2005)
A musical tour of Windsor and surrounding villages in the 18th century, sung and played on period instruments
"Recorded in St Martin's Church, East Woodhay, Berks, April 13th-15th 2005" - Beiheft
Weitere Interpreten: Jenny Thomas (flute & recorder), Oliver Sänding & Michael Sanderson (violins), Katharine May (harpsichord), Ian Gammie (bass viol, guitar, theorbo), Derek McCulloch (narrator & alto)
Keywords: Songs, English / England; Chansons anglaises / Angleterre; Songs, English; England / https://id.oclc.org/worldcat/entity/E39PBJpYDdYvBpjXV6WpybK68C; CD